Proliferation, apoptosis and their regulatory protein expression in colorectal adenomas and serrated lesions. - Jane C Figueiredo (Public Library of Science (PLoS), 2021)
Background Adenomas and serrated lesions represent heterogeneous sets of early precursors in the colorectum with varying malignant potential. They are often distinguished by their histopathologic differences, but little is known about potential differences in regulation of epithelial proliferation and apoptosis. Methods We conducted a protein expression analysis using tissue microarrays of 625 colorectal adenomas and 142 serrated lesions to determine potential differences in regulation of epithelial proliferation and apoptosis. We quantitated proliferation with Ki-67; apoptosis with activated caspase-3 (CASP3); up- and down-regulators of proliferation with cyclin D1, p16INK2, and p21Cip1; and apoptosis regulators with BAX, BCL2, and survivin. Linear mixed effects models and circos diagrams were used to determine relationships among expression and lesion characteristics. Results Adenomas had a significantly higher CASP-3 labeling index (LI) than serrated lesions, resulting in a lower net growth ratio (Ki-67 LI/activated CASP-3 LI, p-value<0.0001). Cyclin D1 LI, p16 LI and p21 LI were lower in adenomas compared to serrated lesions, while expression of both BCL2 and BAX were higher (p <0.001). Among adenomas, cyclin D1 LI and p16 LI levels increased with greater villous component, and the highest BAX expression was detected in adenomas larger than 2 cm (both p<0.0001). Right-sided adenomas had higher CASP3 LI than left colorectal adenomas (p = 0.008). Significant differences in cyclin D1 LI, p21 LI and survivin LI were also observed across histopathologic subtypes of serrated lesions. Conclusions Our findings demonstrate different patterns of regulatory protein expression in adenomas than serrated lesions, especially involving apoptosis. ClinicalTrials.gov Identifier: NCT00272324.